Where There's a Will … : Rural Enslavement and National Register of Historic Places Diversity. (2nd September 2022) - Morgan, Rachel
ABSTRACT: Three archaeological sites in the South Carolina Sandhills provide insight into the opportunities and challenges associated with the archaeology of rural enslavement. A consideration of the material culture and historical context of these sites raises questions about the National Register of Historic Places' standards of significance and integrity and their applicability in historical environments of scarcity. By examining sites with quantitatively small assemblages, but large stories to tell, this article explores prospects for expanding the histories curated in the National Register of Historic Places.